THE INFORMATIVENESS OF METHODS OF RADIATION DIAGNOSTICS IN THE DETECTION OF SKULL FRACTURES - Gasimzade, G.S. (World of Medicine and Biology, 2023)
In 157 (16.2 %) of 969 patients who were injured for various reasons, X-ray diagnostics was performed, in 447 (46.1 %) – CT, in 33 (3.4 %) patients – MRI. The results were subjected to comparative analysis. In total, 167 people were diagnosed with traumatic brain injury. Among patients with identified traumatic brain injuries, X-ray examination was performed in 98 (58.7 %), CT – in 162 (97.0 %), MRI – in 20 (12.0 %) patients. Combined trauma was noted in 63 (88.7 %), isolated trauma – in 8 (11.3 %) patients. Based on the results of the study in detecting head injuries as a result of road accidents, CT can be considered a more effective method due to its sensitivity (89.0 %) and specificity (98.4 %). When detecting a combined traumatic brain injury, MRI due to its specificity (100.0 %), and CT with specificity (96.7 %) and sensitivity (91.8 %) were accepted as more informative methods of examination. It was found that the reformation of CT images in axial and cranial projection allows timely and correct diagnosis of fractures and tomography of the skull bones.
Keywords: traumatic brain injury; combined trauma; radiation diagnostics; sensitivity; specificity